Tribological performance of polydopamine + Ag nanoparticles/PTFE thin films. (April 2020) - Choudhury, Dipankar; Niyonshuti, Isabelle I.; Chen, Jingyi; Goss, Josue A.; Zou, Min
Abstract: This study aims to improve the polytetrafluoroethylene (PTFE) thin film adhesion to stainless steel substrates by incorporating Ag nanoparticles (AgNPs) in a polydopamine (PDA) underlayer. Three different weight percent (1.0 wt%, 1.5 wt%, and 2.0 wt%) of AgNPs were added to the PDA deposition solution, resulting in an increased underlayer roughness. A 3.6-time increase in durability was achieved by adding only 2.0 wt% of AgNPs. Scratch and wear tests demonstrated the improved adhesion and wear resistance of the PDA + AgNPs/PTFE thin films. The improvement was attributed to the increased underlayer roughness, denser fibrillar PTFE network, and enhanced film transfer, all brought by the AgNPs. Graphical abstract: Image 1 Highlights: AgNPs were added to the PDA underlayer to increase its roughness and thus adhesion. Adding AgNPs yielded a smoother and denser PDA + AgNPs/PTFE film than PDA/PTFE film. Adding 2.0 wt% AgNPs to PDA improved the durability of PTFE films 3.6 times. Scratch and wear progression tests revealed improved adhesion and wear resistance. Adding 2.0 wt% AgNPs to PDA enhanced transfer film formed on the counterface ball.